2020
DOI: 10.3390/w12030877
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Potential Evaporation in the Years 1952–2018 in North-Western Poland in Terms of the Impact of Climatic Changes on Hydrological and Hydrochemical Conditions

Abstract: The paper analyses changes in potential evaporation E0 (mm) in north-western Poland in the years 1952–2018. E0 (mm) has been calculated according to Ivanov’s formula based on the monthly values of air temperature (t, °C) and relative air humidity (f, %) for six weather stations of the Institute of Meteorology and Water Management. The data were collected using the Statistica software ver. 13 and the QGIS software ver. 3.80. The results indicate statistically significant trends in the increase of E0 during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…It is related to an increase in air temperature [39,84], which causes higher potential evaporation [76]. Annual potential evaporation in the research area in the years 1952-2018-measured at the meteorological station in Toru ń-increased by 183.9 mm [76]. The authors found that the highest increase occurred in the spring (March-May) and summer (July-September).…”
Section: Changes In Lake Morphology and Water Resourcesmentioning
confidence: 90%
See 2 more Smart Citations
“…It is related to an increase in air temperature [39,84], which causes higher potential evaporation [76]. Annual potential evaporation in the research area in the years 1952-2018-measured at the meteorological station in Toru ń-increased by 183.9 mm [76]. The authors found that the highest increase occurred in the spring (March-May) and summer (July-September).…”
Section: Changes In Lake Morphology and Water Resourcesmentioning
confidence: 90%
“…In the case of many lakes, the process of progressive disappearance associated with a decrease in surface area and water table lowering has accelerated significantly in the 21st century. It is related to an increase in air temperature [39,84], which causes higher potential evaporation [76]. Annual potential evaporation in the research area in the years 1952-2018-measured at the meteorological station in Toru ń-increased by 183.9 mm [76].…”
Section: Changes In Lake Morphology and Water Resourcesmentioning
confidence: 95%
See 1 more Smart Citation
“…Projections of changes of areal ET in the Wielkopolska Region (central-western part of Poland) indicate that the regional average increase in the annual ET is predicted to equal 45 mm, with the highest changes occurring during the winter, when comparing the control period of 1961-1990 to the projection horizon of 2061-2090 [25]. In the north-western part of Poland, significant increasing trends in the potential ET were observed during the period of 1952-2018, as investigated based on data acquired from six weather stations [26]. In this area, particularly high increases were detected during the spring and summer months, explained by a significant increase in air temperature and a decrease in relative humidity, marking the end of the 20th century and the start of the 21st century.…”
Section: Introductionmentioning
confidence: 94%
“…Dość często w pracach polskich agroklimatologów, hydrologów i klimatologów rozmiar parowania lub ewapotranspiracji potencjalnej szacuje się za pomocą formuły Iwanowa (np. Musiał, Bubnowska, Gąsiorek 2007;Kędziora 2008;Radzka 2014;Okoniewska, Szumińska 2020). A.…”
Section: Zmienność Zimowego Wskaźnika Nao a Zmienność Wybranych Eleme...unclassified